Multifocal Gastric Neoplasia after Recurrent Laser Therapy for the Watermelon Stomach - Charles N Bernstein; Norman Pettigrew; Kenneth K Wang; Howard Greenberg; Jeremy Lipschitz (Canadian Journal of Gastroenterology)
Repeated laser therapy has become an accepted therapeutic approach in the treatment of watermelon stomach, and to date no important negative sequelae have been reported. The case of a patient who underwent repeated sessions of neodymium: yttrium aluminum garnet (Nd:YAG) laser therapy over a five-year period for the treatment of the watermelon stomach is presented. Postlaser therapy the patient developed deep ulcerations that would heal; however, he ultimately developed a nodular antrum. Random biopsies of antral nodules revealed carcinoma-in-situ. A Billroth I gastrectomy revealed two foci of carcinoma-in-situ/high grade dysplasia and multiple foci of lower grades of dysplasia. This case suggests a possible association between use of laser therapy and development of gastric neoplasia.